Suitability and Carrying Capacity of Tourism Area in Joint Protection Zone, Wongsorejo Subdistrict, Banyuwangi District - Ervina Wahyu Setyaningrum; Agustina Tri Kusuma Dewi; Endang Dewi Masitoh (Indonesian Journal of Environment and Sustainable Development, 2019)
Coastal area of Banyuwangi district became coral reefs conservation zone to overcome the bombing impact which is often done by the fishermen. This area is managed by Banyuwangi community and called Joint Protection Zone. Aim of this research is to understand suitability and carrying capacity of Bangsring coastal area (Joint Protection Zone) and the research was done by using descriptive method. Method of collecting data is Line intercept transect (LIT). Data analysis stage covered suitability analysis of marine tourism area for snorkeling and diving purposes, carrying capacity analysis. The results show that the marine tourism area of Bangsring Joint Protection Zone is suitable for diving purpose with an area of 1.6 Ha and for snorkeling purpose with an area of 1.7 Ha. Meanwhile, the carrying capacity for diving activity is 8 persons per day and for snorkeling activity is 34 persons per day. So it can be concluded that marine tourism area in the Bangsring Coast (Joint Protection Zone) is in a suitable condition for diving with area of 2,764 Ha and snorkeling with area of 2,764 Ha. Carrying capacity of marine tourism area in the Bangsring Coast (Joint Protection Zone) is 14 people/day for diving and 55 people/day for snorkeling.Keywords: Area Suitability, Coastal, Coral Reef.